Pendidikan Anak Usia Dini Sangat Penting Bagi Tumbuh Kembang Anak - Jusmadi, Evryeni; Fadilla, Rohayu; Mayasari, Henni (Early Childhood Research and Practice, 2025)
The basic concept of early childhood education that develops in modern society. Early childhood education is an effort to educate or provide guidance which is specifically for newborns up to the age of 6 years, which is carried out by stimulating basic education and focusing on the physical and psychological growth and development of a child to form mentality and readiness to enter education. which is further. In general, the purpose of establishing PAUD is to develop various potentials possessed by early childhood as preparation material to be able to adjust and adapt to the surrounding environment.Early childhood education is very important for children and determines the further development of children, because with early childhood education this becomes the foundation for the basis of the child's personality. In addition, early childhood education can also provide readiness for children to face the future, which is closest to the school period. Children who receive early childhood education are different from children who do not receive early childhood education. Children who get early childhood education will learn to be independent individuals, strong in socializing, confident in doing things, have high curiosity and quick to adapt.